Shared Features of the Heimann–Bielshowsky Phenomenon and Ocular Neuromyotonia. (1st November 2020) - Tabba, Subhan; Kini, Ashwini; Al Othman, Bayan; Lee, Andrew G.
ABSTRACT: We describe a case of unusual ocular movement with features of both the Heimann–Bielshowsky Phenomenon and Ocular Neuromyotonia that might suggest that they share some common pathophysiology or be on a spectrum of abnormal firing of ocular motor cranial nerves. We are the first to propose such a relationship.